Comparison of web-based information about cell-free DNA prenatal screening: implications for differences of sex development care - Kim, Soojin; Finney, Esther L.; Naha, Ushasi; Rosoklija, Ilina; Honegger, Kyle S.; Goetsch Weisman, Allison; Holl, Jane L.; Finlayson, Courtney; Chen, Diane; Johnson, Emilie K. (Frontiers in Urology, 2023)
Objective: Cell-free DNA (cfDNA) prenatal screening is a commercially available noninvasive test that detects fetal genetic material in maternal blood. While expectant parents often use it for “gender” determination, there is little information about unintended consequences of testing, such as revelation of a difference of sex development (DSD). The study aimed to characterize currently available website information about cfDNA and compare the cfDNA-related content. Methods: A systematic search for websites with information about cfDNA was conducted using search terms generated by a natural language processing analysis of the results of an Amazon Mechanical Turk (MTurk) survey of 1,000 parents and then performing a “Google” search, using the terms. Data were collected on about each website’s characteristics and information about cfDNA. Information about cfDNA was compared between websites. Data were analyzed using descriptive statistics, Fisher’s exact test or Kruskal-Wallis test were applied, as appropriate. Results: Sixty websites were identified. After eliminating duplicates, 11 commercial company (CC) websites were identified. Nineteen other websites were reviewed of which six overlapped with five CC websites. Most of the websites had non-professional authors (73.7%), such as laypersons and CC representatives. CC websites were significantly more likely than search term-identified websites to state that cfDNA can screen for trisomy 21 (p=0.002), trisomy 18 (p<0.0001), trisomy 13 (p<0.001), sex chromosome aneuploidies (p<0.001), and microdeletions (p=0.002). Conclusions: This study shows that most website currently available information for expectant parents about cfDNA prenatal screening is produced by non-professional organizations. There are significant differences between the information provided by CC and Google search websites, specifically about the number of conditions screened for by cfDNA. Improving availability and quality of information about cfDNA could improve counseling future expectant parents. Inclusion of information about the potential for detection of a DSD is needed.